Efektivitas Program Bimbingan dan Penyuluhan Menggunakan Hypnolearning pada Guru di Sekolah Dasar - Nurjannah, Nurjannah; Alawiyah, Desi; mulkiyan, mulkiyan (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
This study aims to examine the effectiveness of hypnolearning in enhancing teachers' ability to deliver lessons to students through a guidance and counseling program. The research employs an experimental method with a quantitative approach, utilizing a pretest-posttest control group design. The study was conducted at SD Negeri No. 1 Balangnipa, Balangnipa District, Sinjai Regency, from September to October 2024. The population consisted of all elementary school teachers in Gugus II Sinjai Utara, with the sample selected using the total sampling technique to ensure equal opportunities for all members of the population. Data collection techniques included observation and tests, with research instruments comprising pretests and posttests designed to measure changes in teachers' abilities after the intervention. Data analysis was conducted through three stages, including assumption testing (normality and homogeneity tests) and hypothesis testing using a paired sample t-test with a 5% significance level. The results revealed that hypnolearning significantly improved teaching effectiveness, with an average score difference of 24.67742 and a significance value of 0.000 (p < 0.05), indicating a substantial difference between pretest and posttest results. This improvement is attributed to teachers' ability to apply relaxation techniques and provide positive suggestions to students, creating a more conducive learning environment and enhancing students' comprehension. Thus, implementing hypnolearning in guidance and counseling programs has been proven effective in improving teaching quality. Therefore, this method is recommended as an innovative strategy for teachers to create a more comfortable, interactive, and engaging learning experience for students